Running Head: Social Work Developments in Lithuania - Marian Swindell (Social Work and Society, 2004)
Following the end of a half-century of Soviet occupation, Lithuania, like other former Soviet republics, has been in socio-economic disorder. Now that Lithuania is free, the system of social welfare is characterized by under-funded health services and pensions, and a large number of institutions. Semi-structured interviews were conducted with students and practitioners focusing on community development, using Lofland's model of social setting analysis.Results indicate that the collaborative efforts successfully produced a revolutionary and successful social service program, a multi-generational living facility offering full-time social services to unwed mothers, infants, and elderly residents.This article is based upon the qualitative study of social work practitioners and social work students and chronicles the successes and difficulties encountered within the process of community development.